The Correlation Between Mothers' Knowledge About Caesarean Sectio With Mothers' Anxienty During Pre-Surgery at Ummi General Hospital in Bengkulu City - Mepi Sulastri; Kintan Anissa (Utan Kayu Publishing, 2026)
Caesarean section is a surgical delivery method that is increasingly being used. Eventhough considered as general procedure, caesarean section can cause anxienty on mother, especially during pre-operation. One of factor that allegedly influence the anxienty level is Mothers' knowledge about caeserean section. This research purpose is to find out the correlation between Mothers' knowledge about caesarean section with Mothers' anxienty during pre operation at Ummi Hospital of Bengkulu City.This research uses analytic survey method with cross section research design. The research population is all mothers who will choose labor with caesarean section at RSU Ummi of Bengkulu CIty with total sample number 45 respondent who taken by using total sampling technique. Data are collected by using questionnaire about knowledge and anxiety, them analyzed by using univariate and bivariate using Chi-Square test.The research result shows that almost half of respondent has good knowledge (37,8%) and mild anxiety level (40,0%) The result of Chi-Square shows that p-value = 0,008 (p 0,05), means there is a significance correlation between Mothers' knowledge with pre-operation anxiety. It can be concluded that the increase of health education pre-operation is very important to increase the Mothers' knowledge and to reduce anxiety result before conduct caesarean section.